Swelling and Contraction of Phaseolus Hypocotyl Mitochondria - Earnshaw, M. J. (1968)
Isolated Phaseolus mitochondria will swell spontaneously in buffered KCl and contract with an oxidizable substrate or ATP + Mg(2+). The conditions under which the mitochondria are swollen affect subsequent contraction, substrate oxidation and ion accumulation, but not their oxidative phosphorylation ability. Bovine serum albumin reduces the rate of swelling and promotes substrate oxidation, contraction and ion accumulation. Swelling of these mitochondria is associated with the release of malic dehydrogenase and a loss of membrane integrity. The beneficial effects of bovine serum albumin in preserving the energy linked functions of Phaseolus mitochondria is discussed.